Tardigrades Research in Brazil: an overview and updated checklist - Rodolfo Corrêa de Barros (Arquivos de Zoologia, 2020)
Tardigrades are microscopic animals, commonly referred to as “water bears”, and comprise the phylum Tardigrada. They are found in diverse habitats in terrestrial, freshwater and marine environments worldwide. In this paper, it is presented a brief history of the study of tardigrades in Brazil and an updated species checklist of Brazilian tardigrades. Since the first report in 1913, the number of tardigrades records has increased, reflecting advances in the understanding the diversity of tardigrades in Brazil. A total of 100 species known from Brazil are listed, being 30 in marine and 70 in terrestrial and freshwater environments. The records are concentrated in Southeast (47.1%) and Northeast (41.3%) regions. Despite the advances, further research and sampling of new areas is still needed, besides reanalysis and confirmation of old records. Brazil, with its vast territory, extensive continental shelf and great diversity of biomes, has great potential to expand our knowledge of tardigrades fauna.